Malay Islamic Education as a Basis for Religious Moderation in the Nusantara - Nurwahida Nurwahida; Nyayu Soraya; Baldi Anggara (Journal of Educational Sciences, 2026)
Malay Islamic education is a system that emerged from the integration of Islamic values and Malay culture, emphasizing balance between knowledge, practice, and moral conduct. This system functions not only as a means of transmitting religious knowledge but also as a medium for shaping a civilized, tolerant society that upholds human values. In Indonesia’s plural context, these principles align with religious moderation, which emphasizes fairness, balance, and the avoidance of extreme attitudes in understanding religious teachings. This moderation is strongly grounded in the Qur’an, particularly in QS. Al-Baqarah:143, which describes Muslims as ummatan wasathan (a moderate community). Al-Tabari interprets wasath as a just community; Ibn Kathir explains it as the best community that follows the middle path; while al-Qurtubi views it as a form of moderation encompassing tolerance and equilibrium. These values are reflected in Malay Islamic educational traditions such as politeness, mutual cooperation, consultation, and respect for teachers. In the digital era, Malay Islamic education faces social and technological challenges, yet it also holds opportunities to strengthen its identity through curriculum integration of moderation values, revitalization of traditional institutions, and teacher capacity development. Thus, Malay Islamic education plays a vital role in shaping moderate and ethical Muslim communities.